PELATIHAN KOMUNIKASI EFEKTIF BAGI IBU DAN KADER POSYANDU DALAM MENINGKATKAN INTERAKSI POSITIF DENGAN ANAK DI POSYANDU TERATAI 2, CISARANTEN KULON - Wiwin Winarti; Karima Laila Insani; Dwi Zakiy Ade Zuhair; Fauzan Trinoviana Supardi; Zamzam Aulia Urrahmah (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2025)
This community service program aims to improve the knowledge and skills of mothers and posyandu cadres in communicating effectively with children. Many communication barriers occur in early childhood, such as crying, fear, refusal to eat, and anxiety during health procedures. These challenges reflect the limited understanding of parents and cadres regarding child developmental communication cues and strategies. The purpose of this activity was to provide training on effective verbal and nonverbal communication, communication according to the child's age, and practical techniques such as storytelling, role play, and emotional validation. The method consisted of lectures, discussions, case studies, demonstrations, and pre–post tests. The activity was attended by 25 participants, assisted by four students and one lecturer. Results showed an increase in participants’ knowledge from 50% (pre-test) to 95% (post-test). Participants demonstrated increased confidence in handling children’s emotions and communicating during feeding, immunization, and separation situations. This program is expected to strengthen the capacity of cadres and mothers to support healthy communication and child development in the community. Keywords: child communication; community service; health communication; parenting; posyandu